FRI0086 Before Clinically Detectable Arthritis Develops, ACPA-Positive and ACPA-Negative Arthralgia Patients Have Different Symptoms. (15th July 2016) - Burgers, L.E.; van Steenbergen, H.W.; Mangnus, L.; Huizinga, T.W.J.; van der Helm-van Mil, A.H.M.
Abstract : Objectives: Anti-citrullinated protein antibody (ACPA)-positive and ACPA-negative rheumatoid arthritis (RA) have different genetic risk factors and underlying biological mechanisms. Therefore, we hypothesized that patients' characteristics in the symptomatic phase before clinical arthritis has emerged are also different. We investigated this by studying the arthralgia phase of ACPA-positive and ACPA-negative patients. Methods: Patients included in a clinically suspect arthralgia (CSA)-cohort were followed for 2 years or until arthritis development. At inclusion, information on initial symptoms and current symptoms was obtained, physical examination and MRI performed and blood samples taken. A comparison was made between ACPA-positive and ACPA-negative CSA-patients that later developed arthritis. Results: 35 patients (17-ACPA-positive, 18 ACPA-negative) included between April 2012 and May 2015 developed arthritis. 88% of ACPA-negative patients experienced morning stiffness as an initial symptom, compared to 40% of ACPA-positive patients (p=0.01). ACPA-positive patients more often had symptoms in both upper and lower extremities than ACPA-negative patients (35% versus 6%, p=0.03). Important reasons for rheumatologists to identify CSA was morning stiffness in ACPA-negative patients (38% versus 7%, p=0.04) and inflammatory-type arthralgia in ACPA-positive patients (67% versus 19%, p=0.01). ACPA-positive patients had a longer symptom duration at first presentation (median of 22.4 weeks versus 10.6 weeks, Figure 1 ) but converted to arthritis quicker (median 6.9 versus 15.9 weeks after inclusion, p=0.04, Figure 1 ). A combination of variables clustered ACPA-positive and ACPA-negative patients in PLS-analysis. Conclusions: In the phase preceding clinical arthritis, ACPA-negative and ACPA-positive arthralgia patients have different characteristics. This contributes to the notion that ACPA-positive and ACPA-negative RA are different disease subsets. Acknowledgement: The research leading to these results was funded by a Vidi-grant of the Netherlands Organisation for Scientific Research, a grant of the Dutch Arthritis Foundation, a grant of the Dutch Organization of Health Research and the FP7 grant TEAM. Disclosure of Interest: None declared